2020
DOI: 10.7326/m20-2854
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnostics for Severe Acute Respiratory Syndrome–Related Coronavirus 2

Abstract: Accurate serologic tests to detect host antibodies to severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) will be critical for the public health response to the coronavirus disease 2019 pandemic. Many use cases are envisaged, including complementing molecular methods for diagnosis of active disease and estimating immunity for individuals. At the population level, carefully designed seroepidemiologic studies will aid in the characterization of transmission dynamics and refinement of disease bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
166
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(175 citation statements)
references
References 70 publications
4
166
1
4
Order By: Relevance
“…Serologic tests are less likely to be reactive in the first several days to weeks of infection, they have very limited utility for diagnosis in the acute setting [ 62 , 63 ]. If used, checking serology three to four weeks after the onset of symptoms optimizes the accuracy of testing [ 58 ].…”
Section: Laboratory Testing Techniquementioning
confidence: 99%
“…Serologic tests are less likely to be reactive in the first several days to weeks of infection, they have very limited utility for diagnosis in the acute setting [ 62 , 63 ]. If used, checking serology three to four weeks after the onset of symptoms optimizes the accuracy of testing [ 58 ].…”
Section: Laboratory Testing Techniquementioning
confidence: 99%
“…SARS-CoV-2-specific B cell responses typically lead to detectable antibody titers and fully positive rates at about 18 days after the initial onset of symptoms [11]. Seroepidemiological studies can help to catalogue those who have been previously infected (including mild or subclinical infections) and may help identify atrisk populations [12]. Longitudinal analysis of humoral immunity is particularly valuable in persons at high risk for exposure such as HCP.…”
Section: Introductionmentioning
confidence: 99%
“…56 As serological assays become available, patients and HCWs can be tested to identify those who have developed an immunological response. 57 This may include the identification of cases of asymptomatic infection or false-negative RT-PCR. 5759 While it is expected that most COVID-19 patients develop some kind of immune response, it has been shown that antibody titres can be of limited magnitude in up to 30% of cases and absent in up to 6%.…”
Section: Day-after: Adapting To a Lingering Pandemicmentioning
confidence: 99%
“…57 This may include the identification of cases of asymptomatic infection or false-negative RT-PCR. 5759 While it is expected that most COVID-19 patients develop some kind of immune response, it has been shown that antibody titres can be of limited magnitude in up to 30% of cases and absent in up to 6%. 60 Also, it is not clear if existing IgG antibodies are always protective, at what titre, and for how long.…”
Section: Day-after: Adapting To a Lingering Pandemicmentioning
confidence: 99%
See 1 more Smart Citation